The effectiveness of lifestyle training program promoting adolescent health with polycystic ovarian syndrome: A study protocol for a randomized controlled study - Fatemeh Nahidi; Fahimeh Ramezani Tehrani; Delaram Ghodsi; Mahdi Jafari; Hamid Alavi Majd; Somayeh Abdolahian (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Lifestyle training is of a key important in adolescent age for better life in the future. Healthy lifestyle in adolescents can management of any disease such as diabetes and polycystic ovarian syndrome (PCOS). Schools can provide an important environment to identify and change the lifestyle of students. The aim of this protocol is designing and evaluating the effectiveness of school-based lifestyle training program improving the PCOS of adolescents. MATERIALS AND METHODS: A cluster-randomized controlled trial will be conducted to examine the effectiveness of school-based lifestyle training program in 16 to 18 years old adolescent girls. The healthy lifestyle program will be designed by modification of behavioral habit, dietary intake, and physical activity and educated in eight sessions for adolescents and one session for parents in the intervention groups with sixty participants. RESULTS: Changes in primary and secondary outcomes in PCOS and healthy adolescents before and after intervention in the intervention and control groups will be analyzed for evaluation effectiveness by one-way ANOVA or other nonparametric equivalents. CONCLUSION: The current study will provide information on the effectiveness of school-based lifestyle training programs for adolescents. With increasing numbers of PCOS at risk for long-term and/or late effects of treatment and other chronic diseases, efforts for promoting the healthy lifestyle of this important group are urgently needed. This lifestyle program may provide valuable information relating to the development of other healthy lifestyle interventions for PCOS and result in appropriate behavior change and self-management strategies.